Architecture into Theatre and Film Making Process (International Journal of Innovative Research in Engineering & Management, 2022)
The director's desire to make his picture as  true to the tale and place as feasible necessitates the use of  architecture to bring out the authenticity as well as realism  aspect. This paper is based on Architectural involvement  in to theatre and film making process. To understand the  important role of architecture, first go through by the  glimpse of history of world theatre to Indian Sanskrit  theatre. How Indian cinema were origin and presently film  making processes involving with architecture, try to  present in this paper. The relevance of visual design has  been stressed by theatre directors, filmmakers, and  animators. Designers have researched the influence of  character placements, lighting configurations, and camera  movements on transmitting the story, eliciting emotions  and moods, and engaging viewers. Many research  initiatives concentrated on adjusting the narrative material  to the interaction, while the visual presentation received  less attention. Authors introduce a novel method to  interactive storytelling based on filmmaking theory in this  article. The structure is based on principles derived from  filmmaking, cinematography, and visual arts theory. Such  adaptation, the authors propose, will result in improved  engagement and a more interactive story experience.
Keywords: Architecture Involvement; Film making process; History of theatre; Theatre and film making